Core Competence Development Strategy to Achieve Competitive Advantage (Case Study: Dawoon Tea) - Nurfrina Putri, Rizkia; Syarief, Rizal; Asnawi, Yudha Heryawan (School of Business, IPB University (SB-IPB), 2023)
Tea is a type of ready-to-drink beverage that has been attached to people's daily lives. Dawoon Tea is a small enterprise that has the opportunity to have a sustainable competitive advantage. This research aimed to formulate the right core competence development strategy for Dawoon Tea in order to achieve a competitive advantage. The data sources were primary data and secondary data. Primary data such as results of observation and interviews with internal management and also customers help to identify internal discussion, while interviews with other business experts help to identify external discussion. The secondary data used are literature studies such as journals, textbooks, economic and social data. This study used a resource-based view method with VRIO assessment to identify potential resources and competencies that can be developed as internal aspects. In addition, Porter's Five forces method is also used to provide an overview of the threats faced by Dawoon Tea in the industry as external aspects. The results of analysis shows that Dawoon Tea has competencies in production activities and business partner management. In the future, to pursue the target vision and respond to market needs, Dawoon Tea can develop competencies in creating alternative products that are more durable, build reliable investment financial partnership competencies, and also create digital marketing competence. The development of these competencies is expected to encourage Dawoon Tea to achieve its competitive advantage. Keywords: competitive advantage, core competence, resource-based view, VRIO, tea